FENOMENA LINKAGE PENDIDIKAN DI INDONESIA: KAJIAN LITERATUR TENTANG KEMITRAAN DAN KOLABORASI - Anggri Miftahul Jannah; Din, Rustam Ibrahim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The phenomenon of educational linkage in Indonesia has become an important aspect of improving the quality, relevance, and competitiveness of education. Educational linkage encompasses collaboration between educational institutions and the business and industrial sectors, as well as families, communities, government agencies, and other stakeholders. This study aims to describe the phenomenon of educational linkage, identify the challenges encountered, and analyze partnership-strengthening strategies across various levels of education. The study employs a literature review method by examining scientific articles related to educational partnerships, curriculum relevance, school–industry collaboration, school–family and community partnerships, holistic-integrative early childhood education, and university–industry cooperation. The findings reveal that the main challenges include the mismatch between graduates’ competencies and labor market needs, low stakeholder participation, weak partnership communication, limited resources, and insufficient curriculum integration with societal needs. To address these issues, several strategies are recommended, including strengthening multi-stakeholder partnerships, synchronizing curricula with industry demands, utilizing information technology, enhancing educators’ competencies, implementing internship and work-based learning programs, and reinforcing the role of families and communities in education. Strengthening educational linkage is essential for developing high-quality, adaptive human resources that meet contemporary demands through sustainable collaboration among all educational stakeholders